2012
DOI: 10.1007/s10753-012-9574-y
|View full text |Cite|
|
Sign up to set email alerts
|

p-Cymene Modulates In Vitro and In Vivo Cytokine Production by Inhibiting MAPK and NF-κB Activation

Abstract: The present study was designed to investigate the effects of p-cymene on lipopolysaccharide (LPS)-induced inflammatory cytokine production both in vitro and in vivo. The production of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and interleukin-10 (IL-10) in LPS-stimulated RAW 264.7 cells and C57BL/6 mice was evaluated by sandwich ELISA. Meanwhile, the mRNA levels of cytokine genes were examined in vitro by semiquantitative RT-PCR. In a further study, we analyzed the activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 35 publications
0
37
1
Order By: Relevance
“…In C57BL/6 mice, TNF-α and IL-1β were downregulated and IL-10 was upregulated by p-cymene treatment. It also inhibited LPS-induced activation of ERK 1/2, p38, JNK, and IκBα (32,33). …”
Section: Terpenes With Anti-inflammatory Functionmentioning
confidence: 96%
“…In C57BL/6 mice, TNF-α and IL-1β were downregulated and IL-10 was upregulated by p-cymene treatment. It also inhibited LPS-induced activation of ERK 1/2, p38, JNK, and IκBα (32,33). …”
Section: Terpenes With Anti-inflammatory Functionmentioning
confidence: 96%
“…After follicle colonisation, P. acnes induces a suite of inflammatory changes such as the production of cytokines by host tissues and activation of the innate immune response via Toll-like receptor 2 [39,41]. A number of studies have shown in vitro that tea tree oil or major components suppress inflammation [42]. Cytokine production by human monocytes (but not neutrophils) [43,44] and macrophages [45] is inhibited by tea tree oil and the major component terpinen-4-ol [46].…”
Section: Properties Of Tea Tree Oil Contributing To Clinical Efficacymentioning
confidence: 99%
“…17,30,31) We demonstrated that p-cymene suppressed the phosphorylation of ERK1/2 and p38 MAPK in TPA-treated HT-1080 cells, suggesting that the concomitant suppression of the ERK1/2 and p38 MAPK signal pathways by p-cymene at least partially results in the down-regulation of MMP-9 production. Moreover, as monoterpenoids including p-cymene have been reported to potentially inhibit the NF-κB signal pathway, 7,32) the inhibition of NF-κB may be associated with the p-cymene-decreased expression of MMP-9 in TPAstimulated HT-1080 cells. Further experiments are needed to clarify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%